Covalent modification of a ten-residue cationic antimicrobial peptide with levofloxacin - Rodriguez, Carlos A.; Papanastasiou, Emilios A.; Juba, Melanie; Bishop, Barney (Frontiers in Chemistry, 2014)
The rampant spread of antibiotic resistant bacteria has spurred interest in alternative strategies for developing next-generation antibacterial therapies. As such, there has been growing interest in cationic antimicrobial peptides (CAMPs) and their therapeutic applications. Modification of CAMPs via conjugation to auxiliary compounds, including small molecule drugs, is a new approach to developing effective, broad-spectrum antibacterial agents with novel physicochemical properties and versatile antibacterial mechanisms. Here, we’ve explored design parameters for engineering CAMPs conjugated to small molecules with favorable physicochemical and antibacterial properties by covalently affixing a fluoroquinolone antibiotic, levofloxacin, to the ten-residue CAMP Pep-4. Relative to the unmodified Pep-4, the conjugate was found to demonstrate substantially increased antibacterial potency under high salt concentrations. Historically, it has been observed that most CAMPs lose antibacterial effectiveness in such high ionic strength environments, a fact that has presented a challenge to their development as therapeutics. Physicochemical studies revealed that P4LC was more hydrophobic than Pep-4, while mechanistic findings indicated that the conjugate was more effective at disrupting bacterial membrane integrity. Although the inherent antibacterial effect of the incorporated levofloxacin molecules did not appear to be substantially realized in this conjugate, these findings nevertheless suggest that covalent attachment of small molecule antibiotics with favorable physicochemical properties to CAMPs could be a promising strategy for enhancing peptide performance and overall therapeutic potential. These results have broader applicability to the development of future CAMP-antibiotic conjugates for potential therapeutic applications.